Strategi Manajemen Pengembangan Kemampuan Menulis Artikel Bahasa Inggris dalam Menghadapi Era Globalisasi 4.0 (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This study aims to analyze the influence of management strategies for developing the ability to write articles in English on the quality of students' writing. The type of data used is primary data, collected directly from respondents who are students of the management study program at the Faculty of Economics, Kosgoro 1957 Institute of Business and Informatics (IBIK 57) totaling 101 students. Descriptive analysis is used to describe the characteristics of the sample and data distribution, while inferential analysis, such as the coefficient of determination and linear regression, are used to test the relationship between the independent variable (management strategy) and the dependent variable (writing ability). The results of the study indicate that management strategies involving the frequency and quality of training, trainer competence, the use of assistive technology, and evaluation and feedback have a significant influence on improving students' writing skills. These findings emphasize the importance of a structured and focused management approach in developing writing skills, especially in the increasingly competitive era of globalization.